FACTORS AFFECTING THE FINANCIAL PERFOMANCE OF AGRICULTURAL COMPANY’S: EVIDENCE FROM THE INDONESIA STOCK EXCHANGE - Intan, Dian Retno; Malau, Leo Rio Ependi; Rambe, Khoiru Rizqy; Damanik, Mario (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
The Indonesian economy is primarily based on the agriculture sector, even growing when other sectors are down. This role is supported by the existence of agricultural companies that run businesses with profit-oriented goals. The company's ability to generate profits reflects the company's financial performance and is influenced by various factors. Using panel data for the years 2015–2021 from 17 agricultural companies listed on the Indonesia Stock Exchange (IDX), this study aims to determine the influence of internal and external factors on the financial performance of agricultural companies in Indonesia. The results of static panel data regression found that the company's growth and the dummy of the Covid-19 pandemic had a positive and significant effect on the company's financial performance which was proxied through the profitability ratio (ROA). Debt asset ratio (DAR), COGS/sales, and exchange rate have a negative and significant effect on ROA. In general, these results confirm the pecking-order theory in the relationship between ROA and DAR, as well as the ability of agricultural companies in Indonesia to survive in the conditions of the Covid-19 pandemic. The implication for improving the performance of agricultural companies in Indonesia is that companies must be able to reduce the percentage of production costs (COGS/sales) and implement an optimal capital structure mix. Companies are also required to carry out good risk management to anticipate exchange rate fluctuations.